Pemanfaatan Aplikasi Kasir Pos Dalam Pencatatan Dan Pengelolaan Keuangan Umkm - Ningsih, Nurul Hidayati Indra; Tri Yunarni, Baiq Reinelda; Eikman, Alfian; Hadi, Sulhan; Bahri, Saiful; Budiman, Budiman (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Strengthening and mastering financial literacy can increase the ability of MSME actors in managing their business finances. The activity of utilizing the Cashier Application on a cellphone can also facilitate financial recording, so that MSME actors can easily see the reports they need such as, Profit and loss reports, receivables, payables, and others contained in the Irea Lites Post Cashier application. This activity is also an actualization of the Chatur Dharma of Higher Education in the field of community service in responding to the low level of community literacy in the era of the rapidly developing digital world. The goal to be achieved from this community service activity is to increase the financial literacy of MSME actors in Lembar Selatan Village and to be able to improve their businesses. The results of this community service activity are the delivery of information related to how to record business finances, using the Cashier application, how to read financial reports in the Post Cashier Application.